Abwesenheit von Rom: Aristokratische Interaktion in der späten römischen Republik und in der frühen Kaiserzeit - Habenstein, Astrid (Heidelberg University Publishing (heiUP), 2015)
The immense ideological significance that the city of Rome held since the times of the late republic corresponded until the 2nd century AD with the actual supremacy of the urbs within the Imperium Romanum: Rome was the place where socially and politically influential players and groups met; it was where they tried to create an atmosphere of mutual understanding and agreement through complex ways of interaction. Until well into the imperial era the senatorial aristocracy considered the interacting presence of Rome as a major constant of their lifestyle. At least until the 1st century AD the emperors could not disengage themselves from the reference framework that the city was. Therefore, the forms and the reasons for aristocratic and imperial absence are of particular interest. Which role the absence of Rome played in the system of aristocratic interaction and which implications it had for politics and the society of the late republic and the early imperial era is the subject of the present study. Astrid Habenstein's work was awarded by the Historical Institute at the University of Bern with the prize for the best PhD-thesis in 2012.